Defining and predicting service utilisation in young adulthood following childhood treatment of an eating disorder. Issue 3 (May 2020) - McClelland, Jessica; Simic, Mima; Schmidt, Ulrike; Koskina, Antonia; Stewart, Catherine
Abstract : Background: Eating disorder services are often separated into child and adolescent eating disorder services (CAEDSs) and adult eating disorder services (AEDSs). Most patients in CAEDSs present with first-episode illness of short duration, which with appropriate treatment, have a good prognosis. However, some individuals receive further treatment as adults. Little is known about service utilisation in adulthood following childhood/adolescent treatment of an eating disorder. Aims: This study aims (a) to estimate the proportion of patients in a CAEDS who use mental health services as young adults, (b) to delineate service utilisation following treatment in CAEDSs and (c) to identify factors in CAEDSs that predict service utilisation in young adulthood. Method: A consecutive cohort of 322 patients (aged 13–17 years) seen in a CAEDS in the UK over a 5-year period were included in this audit. Data regarding their use of UK-wide adult mental health services as young adults (i.e. when aged 18–25) were extracted from local and national hospital records. Results: A total of 68.3% of CAEDS patients received no mental health treatment as young adults. Although 13% of people seen in a CAEDS had brief eating disorder treatment as young adults, 10% received longer/or more intensive eating disorder treatment. Overall, 10.8% transitioned directly to an AEDS and 7.6% were re-referred following discharge from CAEDS. In our sample, older age and increased use of CAEDSs predicted increased eating disorder treatment in young adulthood. Conclusions: Our results indicate that most people seen in CAEDSs do not receive further mental health treatment as young adults. Several features in CAEDSs distinguish mental health service utilisation in young adulthood, which were identified clinically and could be targeted during treatment.